Global trends of gamification in enhancing students’ social skills in physical education (2015–2025) - Rajip Mustafillah Rusdiyanto; Ari Wibowo Kurniawan (Physical Education and Sports, 2025)
Background: The development of digital technology has triggered a more interactive learning transformation through gamification, namely using game elements to increase students' motivation, engagement, and social skills, such as cooperation, communication, empathy, and problem solving.